Preparation method of boron nitride toughened high-thermal-conductivity silicon nitride ceramic
By depositing boron carbide and magnesium oxide coatings on the surface of boron nitride fibers, combined with ball milling and pneumatic sintering processes, the contradiction between the thermal conductivity and toughness of silicon nitride ceramics is solved, and a high thermal conductivity and high toughness of silicon nitride ceramics are achieved.
Patent Information
- Application Number
- CN202510782688.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-12
- Publication Date
- 2025-07-18
- Estimated Expiration
- 2045-06-12
AI Technical Summary
The prior art is difficult to enhance the thermal conductivity of silicon nitride ceramics while enhancing their toughness, resulting in limitations in engineering applications.
Boron nitride fibers or whiskers are used for toughening, and a double coating of boron carbide and magnesium oxide is deposited on the surface of the boron nitride fibers through unequilibrium magnetron sputtering method to form a weak interface layer. Silicon nitride ceramics are prepared by combining ball milling and air pressure sintering processes.
While maintaining high thermal conductivity, the toughness of silicon nitride ceramics is significantly improved, the flexural strength, fracture toughness and elastic modulus are significantly improved, and the density is moderate.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of silicon nitride ceramics, and particularly relates to a preparation method of a high thermal conductivity silicon nitride ceramic toughened by boron nitride. Background Art
[0002] Silicon nitride (Si3N4) ceramics, based on their excellent mechanical properties, dielectric properties, and thermal shock resistance, have received extensive attention and in-depth research as a popular material in structural ceramics. Due to their relatively excellent comprehensive properties, they have been widely used in fields such as metallurgy, aerospace, energy, machinery, military technology, optics, and the glass industry.
[0003] Si3N4 is a strong covalent bond compound with high atomic binding strength, showing excellent comprehensive properties. In addition, due to the directionality and saturation of covalent bonds, the Si3N4 ceramic has very few slip systems composed of covalent bonds and usually fractures before slip occurs, resulting in obvious brittle characteristics of the Si3N4 ceramic. The fracture toughness of the Si3N4 ceramic is low and very sensitive to local cracks inside the material, which has become a fatal defect of the Si3N4 ceramic, seriously affecting its service life and reliability, and greatly limiting its application range. In order to improve the fracture toughness of the Si3N4 ceramic, the existing technologies mainly focus on material composite design, microstructure regulation, and preparation process optimization. Among them, the better effect is to improve the toughness by adding fibers or whiskers, including second-phase materials such as silicon carbide whiskers, silicon carbide fibers, or boron nitride fibers, and utilize mechanisms such as crack deflection and whisker pull-out to absorb fracture energy.
[0004] Boron nitride fibers / whiskers have excellent high-temperature stability, low dielectric loss, and a low thermal expansion coefficient close to that of silicon nitride, making them a preferred toughening material for silicon nitride ceramics. However, many problems occur when boron nitride fibers / whiskers are compounded into the ceramic matrix, such as strong interfacial reactions between the fibers and the matrix, and a significant decrease in the density of the composite material after the addition of the fibers; the strong interfacial reaction between the fibers and the matrix will weaken the toughening effect. Specifically, in terms of the properties of silicon nitride itself, the higher the sintering temperature (>1700 °C), the better the thermal conductivity and mechanical properties. However, when compounded with boron nitride fibers, in the region with a low sintering temperature (1400 - 1600 °C), an interface is formed between the boron nitride fibers and the silicon nitride matrix through physical bonding and weak chemical bonds. This interface has a moderate bonding strength, which can not only transfer the load but also allow crack deflection or fiber pull-out, and improve the fracture toughness through the energy dissipation mechanism; when the sintering temperature is higher than 1700 °C, boron nitride and silicon nitride form a hard and brittle Si - B - N ternary phase, forming a rigid interface that hinders crack deflection, and brittle fracture occurs after applying an external force, unable to effectively improve the fracture toughness.
[0005] As a new generation of high-temperature structural materials, the contradiction between the excellent thermal conductivity of high-thermal-conductivity silicon nitride ceramics and their inherent brittleness has always restricted their engineering applications. Although toughening by introducing boron nitride fibers or whiskers can significantly improve the fracture toughness of the materials, there is an inherent conflict between the toughening mechanism and the thermal conductivity, making it difficult to balance toughening and high thermal conductivity. To promote the application of high-thermal-conductivity silicon nitride ceramics in more fields, it is urgent to solve the contradiction between their thermal conductivity and strength and toughness. Summary of the Invention
[0006] Aiming at the deficiencies of the existing technology, the present invention provides a preparation method of boron nitride toughened high-thermal-conductivity silicon nitride ceramics. The prepared silicon nitride ceramics can maintain the high thermal conductivity of silicon nitride ceramics while improving their toughness.
[0007] To solve the above technical problems, the technical solutions adopted by the present invention are as follows: A preparation method of boron nitride toughened high-thermal-conductivity silicon nitride ceramics includes the following steps: pretreatment of boron nitride fibers, chemical vapor deposition, raw material mixing, pressing into shape, and gas pressure sintering; The method for pretreating the boron nitride fibers is to ultrasonically clean the boron nitride fibers with ethanol for 18 - 22 min, dry them and then put them into a nitric acid solution, treat them at 60 - 70 °C for 1 - 1.5 h, take them out, wash and dry to obtain activated boron nitride fibers; The diameter of the boron nitride fibers is 5 - 8 μm, and the aspect ratio is 50000 - 80000:1; The concentration of the nitric acid solution is 65 - 68 wt%.
[0008] The method for chemical vapor deposition is to use the unbalanced magnetron sputtering method with boron carbide target and magnesium oxide target as the targets. The method for chemical vapor deposition is to put the activated boron nitride fibers on the sample holder of the magnetron sputtering equipment, evacuate to below 5.0×10 -3 Pa, introduce argon gas at 16 - 18 sccm, apply a bias voltage of -300 - -400 V to the substrate, ionize argon ions to sputter and clean the sample surface for 15 - 20 min to remove oxides and other contaminants on the sample surface, then adjust the substrate bias voltage to -70 - -100 V, set the argon gas flow rate to 25 - 28 sccm, control the current of the boron carbide target to be 1.5 - 2.0 A, deposit for 3.5 - 4 h, then adjust the substrate bias voltage to -180 - -200 V, control the current of the magnesium oxide target to be 1.5 - 2.0 A, keep the argon gas flow rate unchanged, deposit the magnesium oxide surface layer for 15 - 20 min, and after the deposition is completed, take out the fibers and then perform short cutting treatment to obtain composite coating boron nitride fibers; The purity of the boron carbide target is ≥99.95%; The purity of the magnesium oxide target is ≥99.95%.
[0009] The method of mixing the raw materials is as follows: Add α-silicon nitride powder, composite-coated boron nitride fiber, sintering aid, β-silicon nitride seeds and ethanol into a ball milling device. After ball milling for 4 - 6 hours, a silicon nitride suspension is obtained. Filter and dry the suspension to obtain the mixed raw materials; The length of the composite-coated boron nitride fiber is 10 - 15 mm; The sintering aid is composed of Y2O3 and MgF2, and the mass ratio of Y2O3 to MgF2 is 3 - 4:2 - 3; The aspect ratio of the β-silicon nitride seeds is 5 - 8:1; The mass ratio of the α-silicon nitride powder, composite-coated boron nitride fiber, sintering aid, β-silicon nitride seeds and ethanol is 100:10 - 15:5 - 7:3 - 5:70 - 90; The balls and jars used for ball milling are silicon nitride balls and nylon ball milling jars respectively; The ball-to-material ratio is 2 - 4:1.
[0010] The method of pressing and forming is as follows: Put the mixed raw materials into a mold, perform mechanical pressing and forming with a pressure of 60 - 80 MPa, and then perform cold isostatic pressing treatment at a pressure of 120 - 140 MPa for 3 - 5 minutes to obtain a blank.
[0011] The method of gas pressure sintering is as follows: Place the blank in a gas pressure sintering device, use nitrogen as the protective gas, with a pressure of 1.2 - 2.0 MPa, keep it at a temperature of 1700 - 1800 °C for 2 - 3 hours, and obtain silicon nitride ceramics after cooling and releasing the pressure.
[0012] Compared with the prior art, the beneficial effects of the present invention are as follows: The silicon nitride ceramics prepared by the method of the present invention can improve their toughness while maintaining the high thermal conductivity of silicon nitride ceramics. Its thermal conductivity is 79.2 - 81.0 W / (m·K), the flexural strength is 738 - 745 MPa, the fracture toughness is 11.3 - 11.6 MPa·m 1 / 2 , the elastic modulus is 263 - 270 GPa, and the density is 3.09 - 3.15 g / cm 3 . Specific Embodiments
[0013] In order to have a clearer understanding of the technical features, objectives and effects of the present invention, the specific embodiments of the present invention are now described.
[0014] Example 1 A preparation method of boron nitride toughened high thermal conductivity silicon nitride ceramics is as follows: 1. Pretreatment of boron nitride fiber The boron nitride fibers with a diameter of 5 μm and an aspect ratio of 50,000:1 were ultrasonically cleaned with ethanol for 18 min, dried, and then placed in a nitric acid solution with a concentration of 65 wt%, treated at 60 °C for 1.5 h, taken out, cleaned, and dried to obtain the activated boron nitride fibers.
[0015] 2. Chemical vapor deposition Using the non-equilibrium magnetron sputtering method, with a boron carbide target with a purity of 99.95% and a magnesia target with a purity of 99.95% as the target materials, the activated boron nitride fibers were placed on the sample holder of the magnetron sputtering equipment, evacuated to 4.8×10 -3 Pa, argon was introduced at 16 sccm, a bias voltage of -300 V was applied to the substrate, and the sample surface was sputter-cleaned with ionized argon ions for 20 min to remove oxides and other contaminants on the sample surface. Then, the substrate bias voltage was adjusted to -70 V, the argon flow rate was set to 25 sccm, the current of the boron carbide target was controlled at 1.5 A, and deposition was carried out for 4 h. Then, the substrate bias voltage was adjusted to -180 V, the current of the magnesia target was controlled at 1.5 A, and the argon flow rate remained unchanged. The magnesia surface layer was deposited for 20 min. After the deposition was completed and the fibers were taken out, they were subjected to short cutting treatment to obtain the boron nitride fibers with a composite coating.
[0016] 3. Raw material mixing The α-silicon nitride powder, boron nitride fibers with a composite coating, Y2O3, MgF2, β-silicon nitride seeds, and ethanol were added to a ball milling equipment. The balls and jars used for ball milling were silicon nitride balls and nylon ball milling jars respectively. After ball milling for 4 h at a ball-to-material ratio of 2:1, a silicon nitride suspension was obtained. The suspension was filtered and dried to obtain the mixed raw materials; The length of the boron nitride fibers with a composite coating is 10 mm; The aspect ratio of the β-silicon nitride seeds is 5:1; The mass ratio of the α-silicon nitride powder, boron nitride fibers with a composite coating, Y2O3, MgF2, β-silicon nitride seeds, and ethanol is 100:10:3:2:3:70.
[0017] 4. Compression molding The mixed raw materials were placed in a mold and mechanically compression-molded at a pressure of 60 MPa, and then cold isostatically pressed at a pressure of 120 MPa for 5 min to obtain a blank.
[0018] 5. Gas pressure sintering The blank was placed in a gas pressure sintering equipment, using nitrogen as the protective gas, at a pressure of 1.2 MPa, and held at a temperature of 1700 °C for 3 h. After cooling and releasing the pressure, silicon nitride ceramics were obtained.
[0019] Example 2 A preparation method of high thermal conductivity silicon nitride ceramics toughened by boron nitride is as follows: 1. Pretreatment of boron nitride fibers The boron nitride fibers with a diameter of 6 μm and an aspect ratio of 60000:1 were ultrasonically cleaned with ethanol for 20 min. After drying, they were placed in a nitric acid solution with a concentration of 66 wt% and treated at 65 °C for 1.2 h. After taking them out, they were cleaned and dried to obtain activated boron nitride fibers; 2. Chemical vapor deposition Using the non-equilibrium magnetron sputtering method, with a boron carbide target with a purity of 99.98% and a magnesium oxide target with a purity of 99.98% as the target materials, the activated boron nitride fibers were placed on the sample holder of the magnetron sputtering equipment. The vacuum was pumped to 4×10 -3 Pa, argon was introduced at 17 sccm, a bias voltage of -350 V was applied to the substrate, and the sample surface was sputter-cleaned with ionized argon ions for 18 min to remove oxides and other contaminants on the sample surface. Then, the substrate bias voltage was adjusted to -80 V, the argon flow rate was set to 26 sccm, the current of the boron carbide target was controlled at 1.8 A, and deposition was carried out for 3.8 h. Then, the substrate bias voltage was adjusted to -190 V, the current of the magnesium oxide target was controlled at 1.8 A, and the argon flow rate remained unchanged. The magnesium oxide surface layer was deposited for 18 min. After the deposition was completed and the fibers were taken out, they were subjected to short cutting treatment to obtain boron nitride fibers with a composite coating.
[0020] 3. Raw material mixing α-silicon nitride powder, boron nitride fibers with a composite coating, Y2O3, MgF2, β-silicon nitride seeds and ethanol were added to a ball milling equipment. The balls and jars used for ball milling were silicon nitride balls and nylon ball milling jars respectively. After ball milling for 5 h at a ball-to-material ratio of 3:1, a silicon nitride suspension was obtained. The suspension was filtered and dried to obtain mixed raw materials; The length of the boron nitride fibers with a composite coating is 12 mm; The aspect ratio of the β-silicon nitride seeds is 6:1; The mass ratio of the α-silicon nitride powder, boron nitride fibers with a composite coating, Y2O3, MgF2, β-silicon nitride seeds and ethanol is 100:12:3.5:2.5:4:80.
[0021] 4. Compression molding The mixed raw materials were put into a mold and mechanically compression-molded at a pressure of 70 MPa, and then cold isostatically pressed at a pressure of 130 MPa for 4 min to obtain a blank.
[0022] 5. Gas pressure sintering The blank was placed in a gas pressure sintering equipment, with nitrogen as the protective gas, a pressure of 1.6 MPa, and kept at a temperature of 1750 °C for 2.5 h. After cooling and releasing the pressure, silicon nitride ceramics were obtained.
[0023] Example 3 1. Pretreatment of boron nitride fibers The boron nitride fibers with a diameter of 8 μm and an aspect ratio of 80,000:1 were ultrasonically cleaned with ethanol for 22 min, dried, and then placed in a nitric acid solution with a concentration of 68 wt%, treated at 70 °C for 1 h, taken out, cleaned, and dried to obtain activated boron nitride fibers.
[0024] 2. Chemical vapor deposition Using the non-equilibrium magnetron sputtering method, with a boron carbide target with a purity of 99.99% and a magnesia target with a purity of 99.99% as the targets, the activated boron nitride fibers were placed on the sample holder of the magnetron sputtering equipment, evacuated to 3.5×10 -3 Pa, argon was introduced at 18 sccm, a bias voltage of -400 V was applied to the substrate, and the sample surface was sputter-cleaned with ionized argon ions for 15 min to remove oxides and other contaminants on the sample surface. Then, the substrate bias voltage was adjusted to -100 V, the argon flow rate was set to 28 sccm, the current of the boron carbide target was controlled at 2.0 A, and deposition was carried out for 3.5 h. Then, the substrate bias voltage was adjusted to -200 V, the current of the magnesia target was controlled at 2.0 A, and the argon flow rate remained unchanged. The magnesia surface layer was deposited for 15 min. After the deposition was completed and the fibers were taken out, short-cutting treatment was carried out to obtain boron nitride fibers with a composite coating.
[0025] 3. Raw material mixing α-silicon nitride powder, boron nitride fibers with a composite coating, Y2O3, MgF2, β-silicon nitride seeds, and ethanol were added to a ball milling equipment. The balls and jars used for ball milling were silicon nitride balls and nylon ball milling jars respectively. After ball milling for 6 h at a ball-to-material ratio of 4:1, a silicon nitride suspension was obtained. The suspension was filtered and dried to obtain mixed raw materials; The length of the boron nitride fibers with a composite coating is 15 mm; The aspect ratio of the β-silicon nitride seeds is 8:1; The mass ratio of the α-silicon nitride powder, boron nitride fibers with a composite coating, Y2O3, MgF2, β-silicon nitride seeds, and ethanol is 100:15:4:3:5:90.
[0026] 4. Compression molding The mixed raw materials were put into a mold and mechanically compression-molded at a pressure of 80 MPa, and then cold isostatically pressed at a pressure of 140 MPa for 3 min to obtain a blank.
[0027] 5. Gas pressure sintering The blank was placed in a gas pressure sintering equipment, using nitrogen as the protective gas, at a pressure of 2.0 MPa, and held at a temperature of 1800 °C for 2 h. After cooling and releasing the pressure, silicon nitride ceramics were obtained.
[0028] Example 4 A preparation method of boron nitride toughened high thermal conductivity silicon nitride ceramics is as follows: 1. Pretreatment of boron nitride whiskers The boron nitride whiskers with a diameter of 6 μm and an aspect ratio of 500:1 were ultrasonically cleaned with ethanol for 20 min, dried, and then placed in a nitric acid solution with a concentration of 66 wt%. After treatment at 65 °C for 1.2 h, they were taken out, cleaned, and dried to obtain pretreated boron nitride whiskers; 2. Chemical vapor deposition Using the non-equilibrium magnetron sputtering method, with a boron carbide target with a purity of 99.98% and a magnesia target with a purity of 99.98% as the targets, the pretreated boron nitride whiskers were placed on the sample holder of the magnetron sputtering equipment. The vacuum was pumped to 4×10 -3 Pa, argon was introduced at a flow rate of 17 sccm, a bias voltage of -350 V was applied to the substrate, and the sample surface was sputter-cleaned with ionized argon ions for 18 min to remove oxides and other contaminants on the sample surface. Then, the substrate bias voltage was adjusted to -80 V, the argon flow rate was set to 26 sccm, the current of the boron carbide target was controlled at 1.8 A, and deposition was carried out for 3.8 h. Then, the substrate bias voltage was adjusted to -190 V, the current of the magnesia target was controlled at 1.8 A, and the argon flow rate remained unchanged. The magnesia surface layer was deposited for 18 min to obtain boron nitride whiskers with a composite coating.
[0029] 3. Raw material mixing α-silicon nitride powder, boron nitride whiskers with a composite coating, Y2O3, MgF2, β-silicon nitride seeds, and ethanol were added to a ball milling equipment. The balls and jars used for ball milling were silicon nitride balls and nylon ball milling jars respectively. After ball milling for 5 h at a ball-to-powder ratio of 3:1, a silicon nitride suspension was obtained. The suspension was filtered and dried to obtain mixed raw materials; The aspect ratio of the β-silicon nitride seeds is 6:1; The mass ratio of the α-silicon nitride powder, boron nitride whiskers with a composite coating, Y2O3, MgF2, β-silicon nitride seeds, and ethanol is 100:12:3.5:2.5:4:80.
[0030] 4. Compression molding The mixed raw materials were placed in a mold and mechanically compression-molded at a pressure of 70 MPa, and then cold isostatically pressed at a pressure of 130 MPa for 4 min to obtain a blank.
[0031] 5. Gas pressure sintering The blank was placed in a gas pressure sintering equipment, using nitrogen as the protective gas, at a pressure of 1.6 MPa, and held at a temperature of 1750 °C for 2.5 h. After cooling and releasing the pressure, silicon nitride ceramics were obtained.
[0032] Example 5 A preparation method of boron nitride toughened high thermal conductivity silicon nitride ceramics is as follows: 1. Pretreatment of boron nitride fibers The boron nitride fibers with a diameter of 6 μm and an aspect ratio of 60000:1 were ultrasonically cleaned with ethanol for 20 min, dried, and then placed in a nitric acid solution with a concentration of 66 wt%. After treatment at 65 °C for 1.2 h, they were taken out, cleaned, and dried to obtain activated boron nitride fibers.
[0033] 2. Chemical vapor deposition Using the non-equilibrium magnetron sputtering method, with a boron carbide target with a purity of 99.98% as the target material, the activated boron nitride fibers were placed on the sample holder of the magnetron sputtering equipment. The vacuum was pumped to 4×10 -3 Pa, argon was introduced at a flow rate of 17 sccm, a bias voltage of -350 V was applied to the substrate, and the sample surface was sputter-cleaned with ionized argon ions for 18 min to remove oxides and other contaminants on the sample surface. Then, the substrate bias voltage was adjusted to -80 V, the argon flow rate was set to 26 sccm, the current of the boron carbide target was controlled at 1.8 A, and the deposition was carried out for 3.8 h. After the deposition, the fibers were taken out and then subjected to short-cut treatment to obtain boron nitride fibers with a composite coating.
[0034] 3. Raw material mixing α-silicon nitride powder, boron nitride fibers with a composite coating, Y2O3, MgF2, β-silicon nitride seeds, and ethanol were added to a ball milling equipment. The balls and jars used for ball milling were silicon nitride balls and nylon ball milling jars respectively. After ball milling for 5 h at a ball-to-material ratio of 3:1, a silicon nitride suspension was obtained. The suspension was filtered and dried to obtain mixed raw materials; The length of the boron nitride fibers with a composite coating is 12 mm; The aspect ratio of the β-silicon nitride seeds is 6:1; The mass ratio of the α-silicon nitride powder, boron nitride fibers with a composite coating, Y2O3, MgF2, β-silicon nitride seeds, and ethanol is 100:12:3.5:2.5:4:80.
[0035] 4. Compression molding The mixed raw materials were placed in a mold and mechanically compression-molded at a pressure of 70 MPa, and then cold isostatically pressed at a pressure of 130 MPa for 4 min to obtain a blank.
[0036] 5. Gas pressure sintering The blank was placed in a gas pressure sintering equipment, with nitrogen as the protective gas, a pressure of 1.6 MPa, and held at a temperature of 1750 °C for 2.5 h. After cooling and releasing the pressure, silicon nitride ceramics were obtained.
[0037] Example 6 A preparation method of boron nitride toughened high thermal conductivity silicon nitride ceramics is as follows: 1. Pretreatment of boron nitride fibers The boron nitride fibers with a diameter of 6 μm and a fiber length of 12 mm were ultrasonically cleaned with ethanol for 20 min, dried and then placed in a nitric acid solution with a concentration of 66 wt%, treated at 65 °C for 1.2 h, taken out, cleaned and dried to obtain activated boron nitride fibers.
[0038] 2. Raw material mixing The α-silicon nitride powder, activated boron nitride fibers, Y2O3, MgF2, β-silicon nitride seeds and ethanol were added to a ball milling device. The balls and jars used for ball milling were silicon nitride balls and nylon ball milling jars respectively. After ball milling for 5 h at a ball-to-material ratio of 3:1, a silicon nitride suspension was obtained. The suspension was filtered and dried to obtain the mixed raw materials; The aspect ratio of the β-silicon nitride seeds was 6:1; The mass ratio of the α-silicon nitride powder, activated boron nitride fibers, Y2O3, MgF2, β-silicon nitride seeds and ethanol was 100:12:3.5:2.5:4:80.
[0039] 3. Compression molding The mixed raw materials were put into a mold and mechanically compression molded at a pressure of 70 MPa, and then cold isostatically pressed at a pressure of 130 MPa for 4 min to obtain a blank.
[0040] 4. Gas pressure sintering The blank was placed in a gas pressure sintering device, using nitrogen as the protective gas, at a pressure of 1.6 MPa, held at a temperature of 1750 °C for 2.5 h, and the silicon nitride ceramic was obtained after cooling and releasing the pressure.
[0041] Example 7 A preparation method of a boron nitride toughened high thermal conductivity silicon nitride ceramic is as follows: 1. Boron nitride fiber pretreatment The boron nitride fibers with a diameter of 6 μm and a fiber length of 12 mm were ultrasonically cleaned with ethanol for 20 min, dried and then placed in a nitric acid solution with a concentration of 66 wt%, treated at 65 °C for 1.2 h, taken out, cleaned and dried to obtain activated boron nitride fibers.
[0042] 2. Raw material mixing The α-silicon nitride powder, activated boron nitride fibers, Y2O3, MgF2, β-silicon nitride seeds and ethanol were added to a ball milling device. The balls and jars used for ball milling were silicon nitride balls and nylon ball milling jars respectively. After ball milling for 5 h at a ball-to-material ratio of 3:1, a silicon nitride suspension was obtained. The suspension was filtered and dried to obtain the mixed raw materials; The aspect ratio of the β-silicon nitride seeds was 6:1; The mass ratio of the α-silicon nitride powder, activated boron nitride fiber, Y2O3, MgF2, β-silicon nitride seed crystal, and ethanol is 100:12:3.5:2.5:4:80.
[0043] 3. Compression molding Put the mixed raw materials into a mold, perform mechanical compression molding at a pressure of 70 MPa, and then perform cold isostatic pressing at a pressure of 130 MPa for 4 minutes to obtain a blank.
[0044] 4. Gas pressure sintering Place the blank in a gas pressure sintering device, use nitrogen as the protective gas, at a pressure of 1.6 MPa, keep it warm at a temperature of 1500 °C for 2.5 hours, and release the pressure after cooling to obtain silicon nitride ceramics.
[0045] Test example Detect the thermal conductivity, flexural strength, fracture toughness, elastic modulus, and density of the silicon nitride ceramics prepared in Examples 1-7. Among them, the thermal conductivity is measured by the transient plane heat source method, the flexural strength is calculated by the three-point bending method, the fracture toughness is tested by the indentation method, the elastic modulus is measured by the three-point bending method, and the density is detected by the Archimedes drainage method; the test results are shown in Table 1.
[0046] Table 1 Thermal conductivity, flexural strength, fracture toughness, elastic modulus, and density of silicon nitride ceramics
[0047] The present invention uses boron nitride fiber to toughen silicon nitride ceramics. To solve the problem of poor toughening effect caused by the high interfacial force during sintering of boron nitride fiber at temperatures above 1700 °C, a double-layer coating of boron carbide and magnesium oxide is deposited on the boron nitride fiber. A thin layer of magnesium oxide is deposited in 15-20 minutes, and a weak interfacial layer is formed by dissolution to allow the fibers to bond moderately and balance the efficiency of pull-out and load transfer; moreover, magnesium oxide has high stability in a high-temperature nitrogen environment and can inhibit the surface oxidation of boron nitride fiber and maintain the fiber properties. The thermal expansion coefficient of boron carbide is between the radial values of silicon nitride and boron nitride fiber. The boron carbide coating can relieve the interfacial thermal adaptation stress and avoid transverse fracture caused by the high radial thermal expansion coefficient of boron nitride. At the same time, the high hardness of boron carbide can guide the crack to expand along the coating / substrate interface, promote fiber pull-out rather than direct fracture, and improve the toughness of the prepared silicon nitride ceramics.
[0048] In Example 4, boron nitride whiskers were used as toughening materials. Compared with boron nitride fiber toughening materials, the prepared silicon nitride ceramics had slightly higher elastic modulus and fracture toughness, and slightly lower thermal conductivity and flexural strength. Because the fibers formed continuous heat conduction paths, enhancing heat transfer; the long fibers effectively inhibited crack propagation by bridging cracks and bearing loads. The whiskers were short and randomly distributed, and their hindering effect on the main crack was weaker than that of continuous fibers. However, the whiskers could increase fracture toughness through crack deflection, whisker fracture, and a small amount of pull-out, and the effect of increasing fracture toughness was better than that of fibers.
[0049] In Example 5, only a layer of boron carbide coating was deposited on the outside of the boron nitride fibers. The values of thermal conductivity, flexural strength, and fracture toughness were slightly lower than those in Example 2, indicating that a layer of magnesium oxide deposited on the outer surface of the boron carbide coating could improve the thermal conductivity and mechanical properties of the prepared silicon nitride ceramics.
[0050] In Example 6, boron nitride fibers without any treatment were directly used to toughen silicon nitride ceramics. The thermal conductivity, flexural strength, fracture toughness, elastic modulus, and density of the prepared ceramics were all lower than those in Example 2.
[0051] In Example 7, based on Example 6, the sintering temperature was reduced. At a sintering temperature of 1500 °C, the fracture toughness of the prepared silicon nitride ceramics increased, but the thermal conductivity and flexural strength both decreased.
[0052] Finally, it should be noted that the above are only the preferred embodiments of the present invention and are not used to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, for those skilled in the art, they can still modify the technical solutions recorded in the foregoing embodiments, or perform equivalent replacements for some of the technical features. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A preparation method of boron nitride toughened high thermal conductivity silicon nitride ceramics, characterized in that, The preparation method includes the following steps: pretreatment of boron nitride fibers, chemical vapor deposition, raw material mixing, pressing into shape, and gas pressure sintering; The gas-phase deposition method is as follows: using the unbalanced magnetron sputtering method, with boron carbide target and magnesium oxide target as the targets, placing the activated boron nitride fibers on the sample holder of the magnetron sputtering equipment, evacuating to below 5.0×10 -3 Pa, introducing argon at 16 - 18 sccm, applying a bias voltage of -300 to -400 V on the substrate, ionizing argon ions to sputter and clean the sample surface for 15 - 20 min, then adjusting the substrate bias voltage to -70 to -100 V, setting the argon gas flow rate to 25 - 28 sccm, controlling the boron carbide target current at 1.5 - 2.0 A, depositing for 3.5 - 4 h, then adjusting the substrate bias voltage to -180 to -200 V, controlling the magnesium oxide target current at 1.5 - 2.0 A, keeping the argon gas flow rate unchanged, depositing the magnesium oxide surface layer for 15 - 20 min, and after the deposition is completed, taking out the fibers and then performing short cutting treatment to obtain the composite coating boron nitride fibers.
2. The preparation method of a high thermal conductivity silicon nitride ceramic toughened by boron nitride according to claim 1, characterized in that, In the step of chemical vapor deposition, the purity of the boron carbide target is ≥99.95%, and the purity of the magnesium oxide target is ≥99.95%.
3. The preparation method of a high thermal conductivity silicon nitride ceramic toughened by boron nitride according to claim 1, characterized in that, The method for pretreating boron nitride fibers is to ultrasonically clean the boron nitride fibers with ethanol for 18 - 22 min, dry them, then put them into a nitric acid solution, treat them at 60 - 70 °C for 1 - 1.5 h, take them out, wash and dry them to obtain activated boron nitride fibers.
4. The preparation method of a highly thermally conductive silicon nitride ceramic toughened by boron nitride according to claim 3, characterized in that, In the step of pretreating boron nitride fibers, the diameter of the boron nitride fibers is 5 - 8 μm, and the aspect ratio is 50000 - 80000:1; the concentration of the nitric acid solution is 65 - 68 wt%.
5. The preparation method of a high thermal conductivity silicon nitride ceramic toughened by boron nitride according to claim 1, characterized in that, The method for mixing raw materials is to add α-silicon nitride powder, boron nitride fibers with a composite coating, a sintering aid, β-silicon nitride seeds, and ethanol into a ball milling device, ball mill for 4 - 6 h to obtain a silicon nitride suspension, and filter and dry the suspension to obtain mixed raw materials.
6. The preparation method of a high thermal conductivity silicon nitride ceramic toughened by boron nitride according to claim 5, characterized in that, In the step of mixing raw materials, the length of the boron nitride fibers with a composite coating is 10 - 15 mm; the sintering aid is composed of Y2O3 and MgF2, and the mass ratio of Y2O3 to MgF2 is 3 - 4:2 - 3; the aspect ratio of the β-silicon nitride seeds is 5 - 8:1; the mass ratio of α-silicon nitride powder, boron nitride fibers with a composite coating, the sintering aid, β-silicon nitride seeds, and ethanol is 100:10 - 15:5 - 7:3 - 5:70 - 90.
7. The preparation method of a highly thermally conductive silicon nitride ceramic toughened by boron nitride according to claim 5, characterized in that, In the step of mixing raw materials, the balls and jars used for ball milling are silicon nitride balls and nylon ball milling jars respectively; the ball-to-material ratio is 2 - 4:
1.
8. The preparation method of a high thermal conductivity silicon nitride ceramic toughened by boron nitride according to claim 1, characterized in that, The method for pressing into shape is to put the mixed raw materials into a mold, perform mechanical pressing into shape under a pressure of 60 - 80 MPa, and then perform cold isostatic pressing treatment at a pressure of 120 - 140 MPa for 3 - 5 min to obtain a blank.
9. The preparation method of a high thermal conductivity silicon nitride ceramic toughened by boron nitride according to claim 1, characterized in that, The method for gas pressure sintering is to place the blank in a gas pressure sintering device, use nitrogen as the protective gas, at a pressure of 1.2 - 2.0 MPa, keep it warm at a temperature of 1700 - 1800 °C for 2 - 3 h, and obtain silicon nitride ceramics after cooling and releasing the pressure.
Citation Information
Patent Citations
Boron nitride crystal whisker / silicon nitride ceramic composite material and preparation method thereof
CN101555156A
Method for toughening silicon nitride ceramic with boron nitride nanotubes and product prepared with method
CN108298996A
Boron carbide composite material and preparation method and application thereof
CN117567155A
Reinforced coatings and methods of making the same
US20130210299A1
Method for production of silicon nitride sintered body
US4716133A